Understanding the role of solvent properties on reaction kinetics for synthesis of silica nanoparticles - Bari, Atul H.; Jundale, Rajashri B.; Kulkarni, Amol. A. (Chemical Engineering Journal, 2020)
The effect of various alcoholic solvents and their compositions on the size of silica particles synthesized through hydrolysis and condensation of tetraethyl orthosilicate (TEOS) is studied. The alcohols used are: Methanol, ethanol, propanol, i-propanol, butanol, pentanol, hexanol, octanol, decanol and do-decanol. Ethanol was used as a co-solvent with the higher molecular weight alcohols. Silica particles of size between 100 nm and 2 mu m were obtained by changing solvent composition. Concentrations of total soluble silica and silicic acid were measured and used for exploring the kinetics of hydrolysis and condensation reactions. Polarity, steric hindrance and viscosity of solvent were found to have a strong influence on the rate constants and size of silica nanoparticles. An attempt is made to correlate both final particle size and rate constants with dielectric constant, Wiener index and viscosity of the solvent.
Keywords: condensation; Hydrolysis; kinetics; silica particles; Solvents; Stober process